Comparative efficacy of epigallocatechin-3-gallate against H 2 O 2 -induced ROS in cervical cancer biopsies and HeLa cell lines - Sohail Hussain (Contemporary Oncology, 2017)
Aim of the study : Antioxidants play an important role in maintaining physiological homeostasis. Recent literature emphasises the potential therapeutic effects of natural antioxidants that play anti-inflammatory and antioxidant effects applicable in preventing oxidative stress-induced injury, which characterises their pathogenesis. The goal of this study was to evaluate the protective role of EGCG on the HeLa cell line and cancerous cells. Material and methods : The HeLa cell line and cervical cancer biopsies (CCB) were treated with varying doses of antioxidants to determine their effects. Thereafter, hydrogen peroxide (0–10 nM) – an ROS-generating compound – was co-cultured with varying doses of epigallocatechin-3-gallate (EGCG). The effect of this compound on superoxide dismutase (SOD) and glutathione peroxidase (GPx) activity was assessed. Result : The activity of SOD and GPx was protected significantly in the treatment of EGCG in cervical cancer biopsies and HeLa cell line. Hypothesis : It is hypothesised that EGCG has free radical scavenging properties. Conclusions : EGCG protected the activity SOD and GPx equally in cervical cancer biopsies (CCB) and HeLa cell line.